Diagnostic Laparoscopy and its Role in Patients with Chronic Abdominal Pain: Study from a Tertiary Care Hospital - Farrukh Sami, Muhammad Aslam, Muhammad Tahir Ali, Javaid Sajjad Hashmi, Muhammad Tariq Khan, Muhammad Hanif Memon, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find the efficacy of diagnostic laparoscopy and its role in patients with chronic abdominal pain. Study Design: Observational study Place and Duration of Study: Department of General Surgery, Ali Fatima Hospital/Abu Umara Medical & Dental College Lahore from 1st July 2021 to 31st March 2022. Methodology: Seventy patients suffering from chronic abdominal pain were enrolled. An informed written consent was taken from each of them as an approval of participation. The age of the patients was between 20-65 years. Mostly the left side of the abdomen upper-quadrant was opted. Post creation of pneumo-peritoneum a 3 trocar technique which is standardized procedure was applied and a 10mm port through umbilical while two lateral trocars of 5 mm were used. The completed abdominal-cavity was investigated in detail initializing from the liver then gall bladder as well as anterior-surface of stomach and also the spleen. In women uterus as well as Douglas pouch was examined in context to fluid consistency, colour in addition to its site. The specimens were collected and sent to the histopathological lab for analysis. Results: The mean age of the patients was 36±15.3 years with majority were males with 55.71%. Around 45.71% patient’s pain site was at the right lower quadrant while 21.42% had left lower quadrant. The outcomes of laparoscopic investigation showed 27.10% patients to have appendix related pathology, while 19% had bands of adhesion. Conclusion: Laparoscopic proved to be an effective surgical technique in evaluating exact causes of chronic abdominal pain especially in cases where traditional methods have failed to explain the particular cause. Keywords: Bowel movement, Laparoscopy, Recurrent, Prolonged, Well-being